Trabalho e política de qualificação profissional do sistema Prisional: um estudo contextualizado no Presídio Helena Maria da Conceição de Ituiutaba/MG e nas Associações de Proteção e Assistência aos Condenados (APACS) de Ituiutaba e Itaúna/MG - Silva, Camila Maximiano Miranda (2014)
The purpose of the present thesis was to show reflections about the work and the implemented professional qualification policies, especially at the prison houses in Ituiutaba/MG, namely: Helena Maria da Conceição Prison and Association for Protection and Assistance to the Prisoner (APAC). The study was developed by a wide bibliographic research, documental analysis and empiric research through interviews with prisoners that fulfill their sentence at the prison and those in recovering process at APACs from Ituiutaba and Itaúna. We defend the thesis that there is no effective professional qualification at the prison system, despite of the implemented policies. In this thesis, we do not dismiss the importance of the implemented policies for education of the worker who is inside and outside the penal system, but we emphasize the way that he/she is used inside the prisons, referring to the exploitation of the work and the worker, as well as the labor activities developed by the prisoners on the resocialization process. The research put on evidence the voice and perceptions of the prisoners about the imprisonment conditions, the work and the qualification policies implemented on Ituiutaba s prisons and Itaúna s APAC. This study found, specially using the bibliographic and empiric researches, a policy of imprisonment in Brazil and a criminalization of the individuals that are not functional to the capital, once that the vast majority of the prisoners in the penal establishments of the country comes from the classwhich- lives-from-the-work. The research still shows the contempt of State in relation to the prison system and the fight against the criminality. The thesis raised in this study was confirmed by results from the research, analysis of documents about the professional qualification policies and bibliographical study. We have not seen the effective of these policies in Ituiutaba s prisons. The courses given by APACs contemplate a variety of professional qualification that is fragile, rapid and out of order, with the reference to, specially, the re-socialization process and work rehabilitation of the former prisoner, not assuming a dynamic character, capable of making changes, with the human being and the dignity as the point of reference.